Issues Regarding the Nomenclature of D3 Pharmacist in KEPMENDIKTISAINTEKS Number 337/M/KEP/2025: Problematik Nomeklatur D3 Apoteker dalam KEPMENDIKTISAINTEKS Nomor 337/M/KEP/2025 - Syaripah Ulandari; Made Laksmi Meiliana; Dwi Ismayati (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2026)
The issuance of Decree No. 337/M/KEP/2025 concerning Higher Education Providers for Medical and Health Personnel Conducting Competency Tests has sparked controversy due to the use of the nomenclature "D3 Pharmacist". Conceptually and normatively, the term combines the vocational education level (Diploma III) with a professional degree, which in the national higher education and health legal system is placed at the professional education level. This study aims to analyze the problematic nomenclature and its implications for legal certainty, regulatory coherence, and governance of the pharmaceutical profession. The study used a qualitative approach with a literature study method. Data were obtained from relevant laws and regulations, policy documents, and scientific articles, then analyzed using the Miles and Huberman interactive model through the stages of data reduction, data presentation, and conclusion drawing. The results show that the use of the term "D3 Pharmacist" is not aligned with the national qualification framework and regulations that clearly differentiate vocational and professional education. This inconsistency creates regulatory ambiguity, risks double interpretation in policy implementation, and disrupts the formation of professional identity. Furthermore, this contributes to scope-of-practice confusion, weakens licensing and degree protection mechanisms, and creates a legitimacy gap in the healthcare workforce. Therefore, immediate regulatory harmonization is crucial to ensure legal clarity, protect professional standards, and maintain the quality of healthcare services.